Exposing the Vanities-and a Qualified Defense-of Mechanistic Reasoning in Health Care Decision Making - Howick, J (2011)
Philosophers of science have insisted that evidence of underlying mechanisms is required to support claims about the effects of medical interventions. Yet evidence about mechanisms does not feature on dominant evidence-based medicine "hierarchies." After arguing that only inferences from mechanisms ("mechanistic reasoning")-not mechanisms themselves-count as evidence, I argue for a middle ground. Mechanistic reasoning is not required to establish causation when we have high-quality controlled studies; moreover, mechanistic reasoning is more problematic than has been assumed. Yet where the problems can be overcome, mechanistic reasoning can and should be used as evidence. © 2011 by the Philosophy of Science Association. All right reserved.